14,15-Epoxyeicosatrienoic Acid Protect Against Glucose Deprivation and Reperfusion-Induced Cerebral Microvascular Endothelial Cells Injury by Modulating Mitochondrial Autophagy via SIRT1/FOXO3a Signaling Pathway and TSPO Protein - Qu, Youyang; Cao, Jinlu; Wang, Di; Wang, Shu; Li, Yujie; Zhu, Yulan (Frontiers in Cellular Neuroscience, 2022)
Neurovascular system plays a vital role in controlling the blood flow into brain parenchymal tissues. Additionally, it also facilitates the metabolism in neuronal biological activities. Cerebral MECs (microvascular endothelial cells) are involved in mediating progression of the diseases related to cerebral vessels, including stroke. Arachidonic acid can be transformed into EETs (epoxyeicosatrienoic acids) under the catalysis by cytochrome P450 epoxygenase. We have reported that EETs could protect neuronal function. In our research, the further role of 14,15-EET in the protective effects of cerebral MECs and the potential mechanisms involved in OGD (oxygen glucose deprivation) were elucidated. In our study, we intervened the SIRT1/FOXO3a pathway and established a TSPO knock down model by using RNA interference technique to explore the cytoprotective role of 14,15-EET in OGD/R injury. Cerebral MECs viability was remarkably reduced after OGD treatment, however, 14,15-EET could reverse this effect. To further confirm whether 14,15-EET was mediated by SIRT1/FOXO3a signaling pathway and TSPO protein, we also detected autophagy-related proteins, mitochondrial membrane potential, apoptosis indicators, oxygen free radicals, etc. It was found that 14,15-EET could regulate the mitophagy induced by OGD. SIRT1/FOXO3a signaling pathway and TSPO regulation were related to the protective role of 14,15- epoxyeicosatrienoic acid in cerebral MECs. Moreover, we also explored the potential relationship between SIRT1/FOXO3a signaling pathway and TSPO protein. Our study revealed the protective role and the potential mechanisms of 14,15-EET in cerebral MECs under OGD condition.